A Retrospective Study of Double Eyelid Surgery for Sunken Upper Eyelid in Chinese. Issue 2 (March 2021) - Xie, Xiang; An, Yang; Xue, Hongyu; Xie, Hongbin; Zhao, Jianfang; Li, Dong
Abstract : Objective: The aim of this study was to explore the effective technique of double eyelid surgery for mild, moderate, and severe sunken upper eyelid in Chinese. Methods: According to the degree of the sunken upper eyelid, different procedures were performed. For mild sunken upper eyelid, the key technique was named eyelid volume redistribution (EVR)-1 technique, which was advancing or folding the pretarsal orbicularis oculi muscle flap toward up to the upper margin of the incision. For moderate sunken upper eyelid, the EVR-2 technique included EVR-1 technique and releasing orbital fat toward the upper margin of the tarsus. The other surgical steps were the same as conventional double eyelid surgery. For severe sunken upper eyelid, 2 steps were needed. The first step was eyelid volume augmentation (EVA). This technique injected fat into the retroorbicularis oculi fat layer. The second step was conventional double eyelid surgery which was performed 3 to 6 months later. Results: One hundred sixty-seven patients with sunken upper eyelid underwent double eyelid surgery. In addition to the ameliorative recontouring of the sunken deformity, natural double eyelid was created. All patients had no complication, such as infection, skin irregularities, and lumps. The edema, bruising, and temporary ptosis recovered in 2 weeks. The edema resulted from double eyelid surgery, which last about 2 to 3 months. Conclusions: Our study showed that EVR-1, EVR-2, and EVA techniques have stable surgical results for mild, moderate, and severe sunken upper eyelids in Chinese. The procedures are simple, safe, and have less complications and preferable clinical reference value.